Does Information Improve School Accountability? Results of a Large Randomized Trial - Pandey, Priyanka (World Bank, Washington, DC, 2014)
This study evaluates a community-based randomized controlled trial (RCT) to determine the impact of an information campaign on learning and other school outcomes. The study was conducted in three Indian states, Uttar Pradesh (UP), Madhya Pradesh (MP), and Karnataka. UP and MP are two large north and central Indian states, respectively, and lag behind in economic and social outcomes, while Karnataka in southern India is economically and socially more developed. Even though all three states have devolved oversight roles to the community with respect to government schools, they differ in the extent to which such devolution has taken place. The information campaign disseminated state specific information to the community on its oversight roles in schools and education services that parents are entitled to. Information was disseminated in 11-14 public meetings in each treatment village over a period of two and a half years.